Analisis Pelaksanaan Kegiatan Pramuka di SD Negeri 050712 Hinai Kiri - Anisa Padilla; Herawati Herawati; Winda Mey Lestari Munthe; Wulanda Aditiya; Fajar Sidik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education in elementary schools (SD) seeks to build students' social and moral character in addition to their academic skills. The Scout movement is one of the extracurricular activities that have a significant impact on character development. This research aims to examine how Scout activities are carried out at SDN 050712 Hinai Kiri, including elements of activity planning, implementation, and assessment. This research uses descriptive qualitative methods with data obtained through interviews, observation, and literature review. The results of the research show that overall the implementation of Scout activities at SDN 050712 Hinai Kiri went well. Scout extracurricular activities at SDN ‎‎050712 Hinai Kiri are packaged in an interesting way and make a positive contribution to the world of education. However, there are several obstacles in implementing Scout activities at SDN 050712 Hinai Kiri, namely the difficulty of scout leaders in leading classes, the program not running, and the low level of student discipline in participating in Scout activities. It is believed that the findings of this research will help schools and other related parties in improving program standards and effectiveness